Transcriptome Analysis of Pseudomonas aeruginosa Cultured in Human Burn Wound Exudates - Gonzalez, Manuel R.; Ducret, Verena; Leoni, Sara; Fleuchot, Betty; Jafari, Paris; Raffoul, Wassim; Applegate, Lee A.; Que, Yok-Ai; Perron, Karl (Frontiers in Cellular and Infection Microbiology, 2018)
Pseudomonas aeruginosa is a severe opportunistic pathogen and is one of the major causes of hard to treat burn wound infections. Herein we have used an RNA-seq transcriptomic approach to study the behavior of P. aeruginosa PAO1 growing directly on human burn wound exudate. A chemical analysis of compounds used by this bacterium, coupled with kinetics expression of central genes has allowed us to obtain a global view of P. aeruginosa physiological and metabolic changes occurring while growing on human burn wound exudate. In addition to the numerous virulence factors and their secretion systems, we have found that all iron acquisition mechanisms were overexpressed. Deletion and complementation with pyoverdine demonstrated that iron availability was a major limiting factor in burn wound exudate. The quorum sensing systems, known to be important for the virulence of P. aeruginosa, although moderately induced, were activated even at low cell density. Analysis of bacterial metabolism emphasized importance of lactate, lipid and collagen degradation pathways. Overall, this work allowed to designate, for the first time, a global view of P. aeruginosa characteristics while growing in human burn wound exudate and highlight the possible therapeutic approaches to combat P. aeruginosa burn wound infections.